Higher Body Mass Index Is Associated with Subjective Olfactory Dysfunction - Z. M. Patel; J. M. DelGaudio; S. K. Wise (Behavioural Neurology)
Background. Morbidly obese patients demonstrate altered olfactory acuity. There has been no study directly assessing Body Mass Index (BMI) in patients with olfactory dysfunction. Our purpose was to compare BMI in a group of patients with subjective olfactory dysfunction to those without subjective olfactory complaints. Methods. Retrospective matched case-control study. Sixty patients who presented to a tertiary care otolaryngology center with subjective smell dysfunction over one year were identified. Neoplastic and obstructive etiologies were excluded. Demographics, BMI, and smoking status were reviewed. Sixty age, gender, and race matched control patients were selected for comparison. Chi-square testing was used. Results. 48 out of 60 patients (80%) in the olfactory dysfunction group fell into the overweight or obese categories, compared to 36 out of 60 patients (60%) in the control group. There was a statistically significant difference between the olfactory dysfunction and control groups for this stratified BMI (p= 0.0168).  Conclusion. This study suggests high BMI is associated with olfactory dysfunction. Prospective clinical research should examine this further to determine if increasing BMI may be a risk factor in olfactory loss and to elucidate what role olfactory loss may play in diet and feeding habits of obese patients.